Gender Equality Foundation in a Family to Anticipate Abuse - Ismiati, Saptosih (International Journal Labs, 2023)
Domestic violence committed by husbands against wives in the perspective of human rights is a form of action that violates the basic principles of international human rights declaration. The desire for gender equality is expected to apply to the level of the smallest group, namely family life, especially the existence of the family has a very large influence on people's lives so as not to create gender bias. In this case, the family is the first unit and the smallest unit in forming a foundation to form individuals who have qualities so as not to commit violence. The research method used is a descriptive method of analysis, which is a method that has a function to describe or provide an overview of the object being studied either through data or through samples that have been collected as they are, then a form of analysis is carried out and makes a conclusion that applies to the public. The material used in this study is literature material.